Complex skeletal foot malformation in a Samnite “warrior grave” from Abruzzo, southern Italy (8th–5th century BCE) - Luciani, Stefania (International journal of osteoarchaeology, 2024)
This report describes a male skeleton recovered from the Samnite necropolis of Barrea (Abruzzo, 8th–5th century BCE), showing one malformed foot consistent with the diagnosis of unilateral congenital clubfoot associated with tarsal and tarsometatarsal coalitions in the same foot. This finding is particularly noteworthy because tarsal coalitions in congenital equinovarus foot have rarely been reported in medical literature, and to our knowledge, never in the paleopathological record. The recovery of this individual with impaired locomotion from a grave containing a complete array of weapons and armor sheds new light on the occupant's identity and social attitudes toward disabled people in Samnite society. In mortuary archaeology, the correlation between warrior burials and social identity in life of the dead in ancient times is a widely debated issue. Some scholars assert that the weapons in these graves suggest the existence of a warrior class; others propose that the military items of the burial assemblage indicate a high social status or significant power. This study suggests that in Samnite society, physical impairment did not prevent someone from being honored as a warrior or high‐status community member.